2008
DOI: 10.1080/00288330809509952
|View full text |Cite
|
Sign up to set email alerts
|

Stomach contents of common dolphin (Deiphinussp.) from New Zealand waters

Abstract: This paper provides the first report of stomach contents of common dolphin (Deiphinus sp.) from New Zealand waters. We examined 53 stomachs from 42 stranded and 11 by-caught common dolphin from the North Island of New Zealand between 1997 and 2006. Although the diet of by-caught and stranded common dolphin comprised a diverse range of fish and cephalopod species, the prevalent prey were arrow squid Nototodarus spp., jack mackerel Trachurus spp., and anchovy Engraulis australis. Stranded dolphins that originate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Digestion codes were assigned to retrieved prey items (following Meynier et al 2008), and prey species were identified to the lowest possible taxonomic level using published guides (Paulin et al 1989). Individual prey items were counted, identified and individually weighed (to within 0.1 g when possible), and fork lengths (FL) of fish and mantle lengths of cephalopods were measured (to within 0.1 mm) using callipers.…”
Section: Prey Composition Of Dietmentioning
confidence: 99%
“…Digestion codes were assigned to retrieved prey items (following Meynier et al 2008), and prey species were identified to the lowest possible taxonomic level using published guides (Paulin et al 1989). Individual prey items were counted, identified and individually weighed (to within 0.1 g when possible), and fork lengths (FL) of fish and mantle lengths of cephalopods were measured (to within 0.1 mm) using callipers.…”
Section: Prey Composition Of Dietmentioning
confidence: 99%
“…Of approximately 30 odontocete species occurring in New Zealand waters, the diets of only three others have been described: sperm whale, Physeter macrocephalus (Gaskin & Cawthorn 1967;Clarke & MacLeod 1982;Clarke & Roper 1998;Gomez-Villota 2007); pygmy sperm whale, Kogia breviceps (Beatson 2007); and common dolphin, Delphinus sp. (Meynier et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While small groups of common dolphin are present year-round in shallow waters (20 m depth) in some regions [20], they generally exhibit seasonal inshore/offshore movement, residing in coastal waters during spring and summer, before moving further offshore during autumn [20]. Their inshore/offshore migration also occurs on a diel basis, which seems to correspond with the exploitation of different food sources and the movement of prey [25].…”
Section: Introductionmentioning
confidence: 99%
“…), anchovy ( Engraulis australis ), and arrow squid ( Nototodarus spp.) [25]. Their prey preference makes common dolphin susceptible to trawl fisheries targeting the same species [32].…”
Section: Introductionmentioning
confidence: 99%